PERLAKUAN AKUNTANSI UNTUK ASET BERSEJARAH: PENGAKUAN, PENILAIAN DAN PENGUNGKAPANNYA DALAM LAPORAN KEUANGAN STUDI KASUS PADA MUSEUM ANJUK LADANG KABUPATEN NGANJUK - Dessy Wulandari; A.A. Gde Satia Utama (UPT Penerbitan Universitas Jember)
This study aims to determine the accounting treatment applied to the management of heritage assets in Anjuk Ladang Museum, both of recognition, valuation, presentation and disclosures in the financial statements. This research expected to provide clarity on the accounting standards heritage assets which should be implemented by the manager. This study used a qualitative method with case study approach. Data obtained by primary data from interviews and secondary data obtained from the supporting documents. The result of this study present the management of Museum recognizes Heritage Assets with